How do you solve the equation log_3(x+5)-log_3(x-7)=2? Precalculus Solving Exponential and Logarithmic Equations Logarithmic Models 1 Answer GiĆ³ Feb 17, 2015 You can use the following facts: log_aM-log_aN=log(M/N) and: log_ab=x => a^x=b So you get: log_3(x+5)-log_3(x-7)=2 log_3((x+5)/(x-7))=2 (x+5)/(x-7)=3^2 x+5=9(x-7) x-9x=-63-5 -8x=-68 x=68/8=17/2 Answer link Related questions What is a logarithmic model? How do I use a logarithmic model to solve applications? What is the advantage of a logarithmic model? How does the Richter scale measure magnitude? What is the range of the Richter scale? How do you solve 9^(x-4)=81? How do you solve logx+log(x+15)=2? How do you solve the equation 2 log4(x + 7)-log4(16) = 2? How do you solve 2 log x^4 = 16? How do you solve 2+log_3(2x+5)-log_3x=4? See all questions in Logarithmic Models Impact of this question 6996 views around the world You can reuse this answer Creative Commons License